If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-1a + 4) = 12 Reorder the terms: 4(4 + -1a) = 12 (4 * 4 + -1a * 4) = 12 (16 + -4a) = 12 Solving 16 + -4a = 12 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + -4a = 12 + -16 Combine like terms: 16 + -16 = 0 0 + -4a = 12 + -16 -4a = 12 + -16 Combine like terms: 12 + -16 = -4 -4a = -4 Divide each side by '-4'. a = 1 Simplifying a = 1
| 3x+12=12x-13 | | x^2+4=2x+7 | | -(5-3x)-(5-3x)= | | 13+5.5x=3 | | 3(6x+1)=93 | | f(x)=20(1.5)x | | 10(x-5)-2(x-9)=-28 | | -3.2(5d-7)=-17 | | 13u-91=5u | | 3(x+.2)-(2x+.5)=2(x+.3)-.5 | | 70-7x=8-2x | | 0=7x^2-15x-2 | | -3(-8+5x)=54 | | 6x+8-3x=1-12x-13 | | 5(-4x-7)=25 | | 5(x-2)-2(x-3)=3 | | 5x+6=3(2x+1) | | 0=9x^2+20x+4 | | 0.5y-2=0.33y | | 3x-6-2x=2x+12 | | 4x^2-36+80= | | 7x+7=17+6x | | 2/3x-15=45 | | x=105.3+3.78 | | 5x-12=73 | | 3(x+.2)=2(x-.3)+5.2 | | 14x-28=8x+3-10 | | 10a-5+7a-91=4a+20 | | (24x^6y^3)^(1/3) | | 2x-15=10x+3 | | 3x+2y=500 | | 7a-3b+15=0 |